2019
DOI: 10.3390/agronomy9120819
|View full text |Cite
|
Sign up to set email alerts
|

Growth and K Nutrition of Sesame (Sesamum indicum L.) Seedlings as Affected by Balancing Soil Exchangeable Cations Ca, Mg, and K of Continuously Monocropped Soil from Upland Fields Converted Paddy

Abstract: Growth of sesame is known to be limited by poor K nutrition as a result of imbalance in soil exchangeable cations that cause a competitive ion effect in continuous monocropping from upland fields converted paddy. We hypothesized that balancing soil exchangeable cations will improve the K nutrition and growth of sesame plants. Therefore, the specific objectives of this study were to determine the effect of balancing soil exchangeable cations Ca, Mg, and K of continuously monocropped soils on the growth and cati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It has been reported that the content of Ca and Mg in soils is higher than K, which would cause an ionic competition effect between them. Ca and Mg would replace K on the soil colloid, resulting in a K nutrient deficiency in soils [33,34]. As observed in our study, the imbalance of exchangeable cations in soils requires fertilizer dosage calculation based on ideal Ca, Mg, and K saturation ratios, which are in turn based on soil diagnostic results and precise supplementation of Ca, Mg, and K nutrients to successfully mitigate the cation competition effect.…”
Section: Effect Of Balancing Soil Exchangeable Cations Ca Mg and K Ba...mentioning
confidence: 66%
“…It has been reported that the content of Ca and Mg in soils is higher than K, which would cause an ionic competition effect between them. Ca and Mg would replace K on the soil colloid, resulting in a K nutrient deficiency in soils [33,34]. As observed in our study, the imbalance of exchangeable cations in soils requires fertilizer dosage calculation based on ideal Ca, Mg, and K saturation ratios, which are in turn based on soil diagnostic results and precise supplementation of Ca, Mg, and K nutrients to successfully mitigate the cation competition effect.…”
Section: Effect Of Balancing Soil Exchangeable Cations Ca Mg and K Ba...mentioning
confidence: 66%
“…However, as can be seen in the figure, samples with fertiliser had lower Ca values. This lower concentration of Ca could be due to the larger quantities of other cations, such as K competing with Ca and Mg cations [60]. Nevertheless, this is not the case for the pots with 0-20 mm slag since amendments E25 and E50 had extremely high levels of calcium both with and without fertiliser.…”
Section: Soil Amendment and Nutrient Sourcementioning
confidence: 98%
“…The availability and stoichiometry of N and sulfur (S) in soil influence N and S uptake and thus the N/S ratio in crop plant tissues [20][21][22]. Wacal et al [23] reported the influence of soil Ca, Mg, and K and their ratios (Ca/K and Mg/K) on the K nutrition of sesame. Similarly, the mobility of Mg in soil and plants is affected by the soil Ca, K, and NH 4 + [24].…”
Section: Introductionmentioning
confidence: 99%